The zinc finger protein GLI transforms primary cells in cooperation with adenovirus E1A. - Ruppert, J M (1991)
The GLI gene was previously isolated by virtue of its amplification in human glioblastomas. We have now found that GLI expression can result in the in vitro transformation of both primary and secondary rodent cells. When coexpressed with adenovirus E1A, the GLI protein functions analogously to RAS, resulting in the formation of dense foci of cells which are tumorigenic in nude mice.